G310 Canadian and united kingdom/ireland practice patterns in lumbar puncture performance in febrile neonates with bronchiolitis; a PERC and PERUKI study. (May 2019) - Simone, L; Lyttle, MD; Roland, D; Stephens, D; Schuh, S
Abstract : Background: Serious bacterial infections (SBI) in young infants with bronchiolitis are rare. Infants<1 month old with bronchiolitis and fever often receive sepsis screens including lumbar puncture (LP), despite limited data for this practice and lack of clinical practice guidelines for this population. The primary objective of this study was to investigate practice patterns in performance of LPs in the Emergency Department (ED) management of febrile infants aged ≤30 days with bronchiolitis. Methods: A cross-sectional online survey of two national paediatric emergency research networks in Canada (PERC) and the United Kingdom/Ireland (PERUKI) was conducted using a modified Dillman technique. The survey was preceded by a clinical vignette describing a well-appearing, well-hydrated 21-day-old full-term infant with low-grade fever, respiratory findings typical of bronchiolitis, and no perinatal SBI risk features. Results: The response rate from PERC was 169/250 (68%) and 172/201 (86%) from PERUKI. Nine physicians in training were excluded, leaving 332 eligible participants. Although most physicians believe that very young infants with bronchiolitis rarely have meningitis [PERC141/161 (87.6%); PERUKI 154/171 (90%)] and feel comfortable diagnosing bronchiolitis in this age group [PERC 136/161 (84.5%); PERUKI 143/171 (83.6%)], there was significant variation in the proportion who would be likely/very likely to perform an LP [PERC 100/161 (62.1%); PERUKI 15/171 (8.8%)] (p<0.0001).Practice in Canada, <10 years in practice, and lack of comfort with diagnosing bronchiolitis represent multivariable predictors of increased likelihood of doing an LP; OR 23.7 (95% CI 11.7–47.9), 2.3 (95% CI 1.2–4.2) and 0.4 (95% CI 0.2–0.9), respectively. Rapid knowledge of RSV positivity would decrease LP probability from 35.4% to 20.2%. Conclusion: Estimated probability of performing LPs and other interventions in otherwise healthy febrile neonates with bronchiolitis is highly variable between emergency physicians in Canada and the UK/Ireland. The network, <10 years in ED practice, and comfort level with diagnosing bronchiolitis in newborns constitute independent predictors of the likelihood of LP performance.